Beyond Physical Limits: Exploring Inclusive Islamic Education for Children with Physical Disabilities at SLBN 1 Sleman, Indonesia - Wulandari, Mareta; Azizah, Rahma Nurul; Munandar, Arif; Husna, Difa’ul (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2025)
Education is a universal right, extending crucially to children with special needs. This study investigates the characteristics and development of Islamic education services for children with physical disabilities at SLB Negeri 1 Sleman, Yogyakarta. The research aims to understand the implementation of teaching methodologies currently employed at the school. Utilizing a qualitative case study approach, data was collected through observation, interviews, and documentation, followed by rigorous analysis to draw comprehensive conclusions. The findings reveal that students at SLB Negeri 1 Sleman, Yogyakarta, exhibit distinct individual differences and characteristics. The school has effectively provided various educational services and a commendable infrastructure. While educators at the institution have encountered challenges in teaching children with disabilities, they have also successfully identified and implemented solutions. Evaluation and assessment practices primarily involve individualized assessments. Notably, the learning process has yielded instances where educators found inspiration, and students, in turn, demonstrated increased motivation and enthusiasm for learning Islamic Religious Education (PAI).